2018
DOI: 10.1002/btpr.2674
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of continuous nonaffinity capture chromatography for a recombinant enzyme—optimization for a changing perfusion feedstream and comparison to batch processing

Abstract: This work presents the optimization and critical evaluation of continuous capture chromatography in the downstream process of a recombinant enzyme. For the upstream manufacturing of this molecule, a perfusion process was implemented due to benefits for product quality and productivity. This process is, however, characterized by low titer and significant changes over the course of the harvest duration in terms of active enzyme concentration and impurity content. We evaluated the feasibility and benefits of a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition to single‐column batch chromatography, recent studies on continuous Protein A chromatography with multiple columns have also demonstrated significantly improved productivity and resin capacity utilization. [ 8,12–30 ] Baur et al. [ 19 ] compared the performance of batch, two‐column CaptureSMB, and three‐ and four‐column periodic counter‐current chromatography (PCC) capture processes with a shrinking‐core adsorption model.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to single‐column batch chromatography, recent studies on continuous Protein A chromatography with multiple columns have also demonstrated significantly improved productivity and resin capacity utilization. [ 8,12–30 ] Baur et al. [ 19 ] compared the performance of batch, two‐column CaptureSMB, and three‐ and four‐column periodic counter‐current chromatography (PCC) capture processes with a shrinking‐core adsorption model.…”
Section: Introductionmentioning
confidence: 99%